Unicystic Ameloblastoma: An Unusual Case Report - Sreepreeti Champatyray1 , Saurjya Ranjan Das2 , Neeta Mohanty4 , Jagannath Patro5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Ameloblastomas have many microscopic and clinical variations. Typically it has three biologic variants whichinclude solid, cystic and peripheral, out of which 14% to 22% of all cases are unicystic. Rare variantslikegranular cell subtype composed exclusively of eosinophilic granular cells present inboth peripheral andinner layers of tumoral islands. This is a unique case of cystic ameloblastoma affecting a 16-year-old malewith an unusual radiographic and microscopic pattern. This rare variant will create awareness for oral andmaxillofacial pathologists for a proper pathway of diagnosis.